Proceedings of the 14th International Conference on Interaction Design and Children 2015
DOI: 10.1145/2771839.2771905
|View full text |Cite
|
Sign up to set email alerts
|

Kiteracy

Abstract: Kiteracy is an educational kit designed to improve the literacy process of children with Down syndrome by enabling higher levels of interaction. The kit is based on two Spanish literacy methods: global and phonics. In this work, we present a qualitative study based on video-recorded sessions with twelve children from a Down syndrome institution. The study analyzes three forms of interactions: cardboard, multi-touch and tangible. The task carried out by special education teachers and children in the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 13 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Regardless of the interactive platform, these works only consider tangible interactions on the digital screen. In this respect, Jadan-Guerrero et al (Jadan-Guerrero, Jaen, Carpio, & Guerrero, 2015) conduct a comparison between a touch and a tangible interface for tablets in which touch occurred on screen whereas tangible interactions take place around the device, thus preventing screen occlusion. The evaluation conducted focuses on the experience children with Down syndrome had with a literacy application, and results suggest tangible manipulations being easier as well as fostering more verbalizations.…”
Section: Comparison Of Tactile and Tangible Interactionsmentioning
confidence: 99%
“…Regardless of the interactive platform, these works only consider tangible interactions on the digital screen. In this respect, Jadan-Guerrero et al (Jadan-Guerrero, Jaen, Carpio, & Guerrero, 2015) conduct a comparison between a touch and a tangible interface for tablets in which touch occurred on screen whereas tangible interactions take place around the device, thus preventing screen occlusion. The evaluation conducted focuses on the experience children with Down syndrome had with a literacy application, and results suggest tangible manipulations being easier as well as fostering more verbalizations.…”
Section: Comparison Of Tactile and Tangible Interactionsmentioning
confidence: 99%
“…Few works can be found in the literature focused on the use of multi-touch devices by DS children. Jadan-Guerrero et al (2015) presented the Kiteracy framework to help in literacy learning. They compared three interaction methodologies; cardboard, multi-touch and tangible and their results showed that in the traditional cardboard approach the teachers take control of the activity, in the tangible approach children take control and in the multi-touch approach the control is shared by the children and teachers.…”
Section: Multi-touch Technology Studiesmentioning
confidence: 99%
“…Examples include interactive tables that teach numeracy skills [61]; smartphone applications that assist with nutritional management [47]; and social robotics to teach computational thinking through programming [30]. Some technologies designed to support children with DS are virtual reality Wii games to improve sensorimotor functions alongside therapists [2,60,74]; computer/tablet/smartphone applications that teach literacy or mathematical skills tailored to children's learning abilities and patterns [1,22,59,64]; and tangible interfaces to assist children in learning literacy skills by promoting active participation [32,37]. However, children and adults with DS require different types and levels of assistance.…”
Section: Introductionmentioning
confidence: 99%